Aromatic carboxyl functionalized cellulose separator and its preparation method and application
Patent Information
- Application Number
- CN202611186851.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-30
AI Technical Summary
然而,天然纤维素表面官能团类型较为单一,离子传输能力有限,同时在膜材料成型及结构调控过程中加工性能较差,严重限制了其在高性能锌离子电池隔膜中的进一步应用
1)本发明提供了一种芳香羧基功能化纤维素隔膜的制备方法,通过对纤维素基体进行官能团接枝,获得了结构稳定、低溶胀且离子选择性良好的芳香羧基功能化纤维素基隔膜,实现了其作为水系锌离子电池隔膜的应用。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery separator material technology, specifically relating to an aromatic carboxyl functionalized cellulose separator and its preparation method, as well as the application of the separator in aqueous zinc-ion batteries. Background Technology
[0002] Rechargeable aqueous zinc-ion batteries possess advantages such as abundant zinc resources, low cost, and the inherent safety of aqueous electrolytes, making them one of the most promising next-generation large-scale energy storage systems. However, zinc metal exhibits low thermodynamic stability in aqueous environments, and uneven deposition and interfacial side reactions easily occur during deposition / dissolution, leading to decreased reaction reversibility and ultimately limiting the battery's cycle stability. Therefore, improving the reversibility of the zinc anode deposition / dissolution process is crucial for promoting the practical application of aqueous zinc-ion batteries. To improve zinc anode deposition behavior, researchers have proposed various strategies, including electrolyte optimization, electrode structure control, interfacial protective layer construction, and functional membrane development. Among these, the membrane, as a crucial component connecting the electrolyte and electrode, not only provides electronic insulation but also allows for adjustments to Zn... 2+ Transmembrane migration processes influence ion flux distribution and deposition behavior at electrode interfaces, thus becoming an important research direction in recent years. By rationally designing the membrane structure, ion flux distribution and Zn deposition can be controlled. 2+ This increases the migration rate and creates a more stable local environment near the electrode interface, thereby improving zinc deposition uniformity and reducing the probability of interfacial side reactions.
[0003] Cellulose nanofibers have broad application prospects in the field of functional membranes for aqueous zinc-ion batteries due to their wide availability, renewability, excellent biocompatibility, superior mechanical properties, abundant hydroxyl groups on their surface, and ease of chemical modification. However, the surface functional groups of natural cellulose are relatively simple, resulting in limited ion transport capacity. Furthermore, its poor processing performance during membrane material molding and structure control severely restricts its further application in high-performance zinc-ion battery membranes. Therefore, developing a cellulose functional membrane material with high ion transport capacity, high chemical stability, and scalable preparation is of great significance. Summary of the Invention
[0004] To address the problems and deficiencies of the existing technology, this invention proposes an aromatic carboxyl functionalized cellulose membrane with adjustable structure, high ion conductivity, and high stability.
[0005] The present invention also provides a method for preparing the above-mentioned aromatic carboxyl functionalized cellulose separator, and the application of the separator in an aqueous zinc-ion battery.
[0006] The present invention adopts the following technical solution: On the one hand, this application provides a method for preparing an aromatic carboxyl-functionalized cellulose membrane, which includes the following steps: (1) Using cellulose as raw material, cyanoethylation is carried out in an aqueous system of acrylonitrile and sodium hydroxide. Specifically, cellulose is added to an aqueous system of acrylonitrile and sodium hydroxide to carry out a cyanoethylation reaction. After neutralization and washing, cyanoethylated cellulose is obtained. (2) The cyanoethylated cellulose obtained in step (1) is reacted with a mixed solution of hydroxylamine hydrochloride and sodium hydroxide (i.e., the cyanoethylated cellulose is placed in a reaction system composed of hydroxylamine hydrochloride and sodium hydroxide for conversion reaction), and then washed and freeze-dried to obtain aminooxime cellulose; (3) The aminooxime cellulose obtained in step (2) is dispersed in dimethyl sulfoxide, and phthalic anhydride and potassium ethoxide are added in sequence to carry out addition-cyclization reaction. The reaction product is precipitated, acidified, refluxed in acidic aqueous solution and washed to obtain aromatic carboxyl functionalized cellulose product. (4) The aromatic carboxyl functionalized cellulose product obtained in step (3) is subjected to ultrasonic dispersion, vacuum filtration, drying to form a film and alkaline solution deprotonation treatment, and finally washed and dried to obtain an aromatic carboxyl functionalized cellulose membrane.
[0007] Specifically, in step (1), the amount of cellulose used is 1-3 g, the amount of acrylonitrile used is 36-108 mL, and the mass fraction of sodium hydroxide aqueous solution is 10%-15%, with a volume of 1-3 mL; the temperature of the cyanoethylation reaction is 10-30 ℃, and the reaction time is 6-12 h; after the reaction, a 1-3% acetic acid solution is used for neutralization. For example, the specific operation can be, but is not limited to, adding 1 g of cellulose to 36 mL of acrylonitrile and adding 1 mL of a 10% acetic acid aqueous solution, reacting at 10-30 ℃ for 12 h. After the reaction, a 1% acetic acid solution is used for neutralization, with a volume of 10±3 mL of acetic acid solution, followed by washing with deionized water to obtain cyanoethylated cellulose.
[0008] Specifically, in step (2), the concentration of hydroxylamine hydrochloride in the mixed solution is 1-2 M, and the concentration of sodium hydroxide is 1-2 M; the cyanoethylated cellulose is soaked in the mixed solution for 2-6 h, and then stirred at 70±10℃ for 24±12 h. For example, the specific operation can be, but is not limited to: adding the cyanoethylated cellulose obtained in step (1) to the mixed solution of hydroxylamine hydrochloride and sodium hydroxide, soaking for 2-6 h, and then stirring vigorously at 70℃ for 24 h. After the reaction is completed, the cellulose is washed with deionized water to remove residual reactants, and then dried by freeze-drying (freeze-drying at -50±20℃ for 72±24 h) to obtain amine oxime cellulose.
[0009] Specifically, in step (3), the aminooxime cellulose is prepared into a dimethyl sulfoxide dispersion with a mass fraction of 2% to 5% aminooxime cellulose; the molar ratio of phthalic anhydride to the aminooxime group in the aminooxime cellulose is 1 to 10:1; and the molar ratio of potassium ethoxide to the aminooxime group in the aminooxime cellulose is 1 to 20:1.
[0010] Further, in step (3), after adding phthalic anhydride, the reaction is carried out at 10-30 °C for 2-6 h, and then potassium ethoxide is added and reacted at room temperature for 0.5-3 h; after the reaction is completed, the mixture is precipitated with water, acidified with 1-2 M hydrochloric acid to pH 1-2, and then heated under reflux in a 0.1-1.0 M sulfuric acid aqueous solution for 12±2 h. For example, the specific operation can be, but is not limited to: dispersing the aminooxime cellulose obtained in step (2) in dimethyl sulfoxide to form a dispersion with a mass fraction of 2%-5%, then adding phthalic anhydride and reacting at 10-30 °C for 2-6 h; then adding potassium ethoxide and reacting at room temperature for 0.5-3 h to carry out the addition-cyclization reaction. After the reaction was completed, the reaction system was treated with water precipitation and acidified with 1 M hydrochloric acid to a pH of 1-2. Then, it was heated under reflux in 0.1-1.0 M sulfuric acid aqueous solution for 12 h. After washing with deionized water, aromatic carboxyl functionalized cellulose products were obtained.
[0011] Specifically, in step (4), the deprotonation treatment includes soaking in an alkaline solution, wherein the alkaline solution is at least one of sodium hydroxide solution and potassium hydroxide solution; the concentration of the alkaline solution is 0.1~2.0 M, and the soaking time is 0.5~12 h. For example, the specific operation can be, but is not limited to, the following: the aromatic carboxyl functionalized cellulose product obtained in step (3) is ultrasonically dispersed, then vacuum filtered to form a primary cellulose membrane, and after drying to form a membrane, it is soaked in an alkaline solution of 0.1~2.0 M for 0.5~12 h for deprotonation treatment, and then washed and dried to obtain an aromatic carboxyl functionalized cellulose membrane. This membrane has good hydrophilicity, ion transport performance and interface regulation ability, which is beneficial to improving the cycle stability and electrochemical performance of zinc-ion batteries.
[0012] Secondly, this application provides an aromatic carboxyl-functionalized cellulose separator, wherein the aromatic carboxyl-functionalized cellulose separator is prepared using the above-described preparation method. This separator uses cellulose nanofibers as a matrix, and functional groups are introduced through cyanoethylation, ammonium oximeization, and addition-cyclization reactions. After deprotonation treatment with an alkaline solution, the separator exhibits good hydrophilicity and zinc ion transport regulation capabilities, thus making it suitable for high-performance zinc-ion battery systems.
[0013] Thirdly, this application also provides the application of the above-mentioned aromatic carboxyl functionalized cellulose membrane as a membrane in the preparation of high-performance aqueous zinc batteries.
[0014] Fourthly, this application also provides a battery comprising the aforementioned aromatic carboxyl-functionalized cellulose membrane. Furthermore, the battery can be a zinc-symmetric battery or a zinc-ion full battery, etc.
[0015] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1) This invention provides a method for preparing an aromatic carboxyl functionalized cellulose membrane. By grafting functional groups onto a cellulose matrix, an aromatic carboxyl functionalized cellulose membrane with stable structure, low swelling and good ion selectivity is obtained, enabling its application as a membrane for aqueous zinc-ion batteries.
[0016] 2) The aromatic carboxyl functionalized cellulose membrane prepared by this invention can regulate the interfacial interaction between the membrane / electrolyte / zinc anode, optimize the zinc ion transport path and uniformly distribute ions at the interface, thereby reducing side reactions and concentration polarization of the zinc anode, inhibiting zinc dendrite growth, and improving the reversibility of zinc deposition / stripping.
[0017] 3) The aromatic carboxyl functionalized cellulose membrane prepared by this invention enables aqueous zinc-ion batteries to exhibit excellent cycle performance and rate performance. At the same time, the preparation process is mild and controllable, easy to operate, and has good repeatability. It does not require complex equipment and has the potential for large-scale production, providing a new membrane modification idea for constructing long-life and high-safety aqueous zinc-ion batteries. Attached Figure Description
[0018] Figure 1 The FTIR spectrum of the aromatic carboxyl functionalized membrane prepared in Example 1 of this invention; Figure 2 The image shows the XRD pattern of the aromatic carboxyl functionalized membrane prepared in Example 1 of this invention. Figure 3 The images show the SEM and EDS images of the aromatic carboxyl functionalized membrane prepared in Example 1 of this invention. Figure 4 This is a graph showing the ionic conductivity of the aromatic carboxyl functionalized membrane prepared in Example 1 of the present invention. Figure 5 This is a Tafel curve of the aromatic carboxyl functionalized membrane prepared in Example 1 of the present invention; Figure 6 The symmetrical battery assembled using the aromatic carboxyl functionalized separator prepared in Example 1 of this invention operates at 1 mA cm⁻¹. -2 Cyclic characteristics at current density; Figure 7The full cell assembled using the aromatic carboxyl functionalized separator prepared in Example 1 of this invention was tested at 1 A g. -1 ~5 A g -1 Rate performance at current density; Figure 8 The full cell assembled using the aromatic carboxyl functionalized separator prepared in Example 1 of this invention was tested at 3 A g. -1 Cycling curves at a current density of 4000 cycles. Detailed Implementation
[0019] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] Unless otherwise specified, the experimental methods used in the following experimental examples are conventional methods; the materials and reagents used are commercially available unless otherwise specified.
[0021] Room temperature refers to 25±5℃. Example 1
[0022] The preparation method of an aromatic carboxyl functionalized cellulose membrane according to this embodiment includes the following steps: (1) 1 g of cellulose was added to 36 mL of acrylonitrile, and 1 mL of 10% sodium hydroxide aqueous solution was added. The mixture was stirred magnetically at 25 °C for 12 h. After the reaction was completed, the mixture was neutralized with 10 mL of 1% acetic acid solution and washed with deionized water to obtain cyanoethylated cellulose. (2) The cyanoethylated cellulose obtained in step (1) was soaked in a mixed solution of 1.7 M hydroxylamine hydrochloride and 1.7 M sodium hydroxide for 2 h and stirred vigorously at 70 °C for 24 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water, and freeze-dried at -50 °C for 72 h to obtain amine oxime cellulose. (3) Disperse the aminooxime-modified cellulose obtained in step (2) in dimethyl sulfoxide to prepare a 2% dimethyl sulfoxide dispersion; add phthalic anhydride and react at 30 °C for 4 h, wherein the molar ratio of phthalic anhydride to aminooxime groups in aminooxime-modified cellulose is 5:1; then add potassium ethoxide and react at room temperature for 1 h, wherein the molar ratio of potassium ethoxide to aminooxime groups in aminooxime-modified cellulose is 13:1; after the reaction is completed, pour the reaction solution into 400 mL of deionized water to precipitate, and adjust the pH to 1 with hydrochloric acid; place the obtained precipitate in 0.5 M sulfuric acid aqueous solution and heat under reflux for 12 h, wash with deionized water until neutral, and then redisperse in deionized water to obtain an aromatic carboxyl functionalized cellulose suspension; (4) After the aromatic carboxyl functionalized cellulose suspension obtained in step (3) is ultrasonically dispersed evenly, it is vacuum filtered and the cellulose is deposited on the surface of the filter paper to form a wet film. The wet film and the filter paper are dried at 60 °C for 8 min. After drying, the film is peeled off from the surface of the filter paper with tweezers to obtain a self-supporting membrane. The obtained membrane is immersed in 1 M potassium hydroxide solution at room temperature for 12 h to perform deprotonation and ion exchange. Then, the obtained membrane is washed with deionized water and soaked at least 3 times with deionized water, each soaking time not less than 6 h. After soaking, the obtained membrane is dried at 60 °C for 8 min to obtain an aromatic carboxyl functionalized cellulose membrane, denoted as CNF-Ph. Example 2
[0023] The preparation method of an aromatic carboxyl functionalized cellulose membrane according to this embodiment includes the following steps: (1) Using 2 g of cellulose as raw material, add 72 mL of acrylonitrile and 2 mL of sodium hydroxide aqueous solution with a mass fraction of 10% and stir magnetically at 25 °C for 12 h; after the reaction is completed, neutralize with 20 mL of acetic acid solution with a mass fraction of 1% and wash with deionized water to obtain cyanoethylated cellulose; (2) The cyanoethylated cellulose obtained in step (1) was soaked in a reaction system consisting of 1.7 M hydroxylamine hydrochloride and 1.7 M sodium hydroxide for 2 h and stirred vigorously at 70 °C for 24 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water, and freeze-dried at -50 °C for 72 h to obtain aminooxime cellulose. (3) The aminooxime-modified cellulose obtained in step (2) was uniformly dispersed in dimethyl sulfoxide to prepare a 2% dimethyl sulfoxide dispersion; phthalic anhydride was added and reacted at 30 °C for 4 h, wherein the molar ratio of phthalic anhydride to aminooxime groups in aminooxime-modified cellulose was 5:1; potassium ethoxide was added and reacted at room temperature for 1 h, wherein the molar ratio of potassium ethoxide to aminooxime groups in aminooxime-modified cellulose was 13:1; after the reaction was completed, the reaction solution was poured into 400 mL of deionized water to precipitate, and the pH was adjusted to 1 with hydrochloric acid; the precipitate was placed in 0.5 M sulfuric acid aqueous solution and heated under reflux for 12 h, washed with deionized water until neutral, and then redispersed in deionized water to obtain an aromatic carboxyl functionalized cellulose suspension; (4) After the aromatic carboxyl functionalized cellulose suspension obtained in step (3) is ultrasonically dispersed evenly, it is vacuum filtered and the cellulose is deposited on the surface of the filter paper to form a wet film. The wet film and the filter paper are dried at 60 °C for 8 min. After drying, the film is peeled off from the surface of the filter paper with tweezers to obtain a self-supporting membrane. The obtained membrane is immersed in 1 M potassium hydroxide solution at room temperature for 12 h to perform deprotonation and ion exchange. Then, the obtained membrane is washed with deionized water and soaked at least 3 times with deionized water, and each soaking time is not less than 6 h. After soaking, the obtained membrane is dried at 60 °C for 8 min to obtain an aromatic carboxyl functionalized cellulose membrane. Example 3
[0024] The preparation method of an aromatic carboxyl functionalized cellulose membrane according to this embodiment includes the following steps: (1) Using 3 g of cellulose as raw material, add 108 mL of acrylonitrile and 3 mL of sodium hydroxide aqueous solution with a mass fraction of 10% and stir magnetically at 25 °C for 12 h; after the reaction is completed, neutralize with 30 mL of acetic acid solution with a mass fraction of 1% and wash with deionized water to obtain cyanoethylated cellulose; (2) The cyanoethylated cellulose obtained in step (1) was soaked in a reaction system consisting of 1.7 M hydroxylamine hydrochloride and 1.7 M sodium hydroxide for 2 h and stirred vigorously at 70 °C for 24 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water, and freeze-dried at -50 °C for 72 h to obtain aminooxime cellulose. (3) The aminooxime-modified cellulose obtained in step (2) was uniformly dispersed in dimethyl sulfoxide to prepare a 2% dimethyl sulfoxide dispersion; phthalic anhydride was added and reacted at 30 °C for 4 h, wherein the molar ratio of phthalic anhydride to aminooxime groups in aminooxime-modified cellulose was 5:1; potassium ethoxide was added and reacted at room temperature for 1 h, wherein the molar ratio of potassium ethoxide to aminooxime groups in aminooxime-modified cellulose was 13:1; after the reaction was completed, the reaction solution was poured into 400 mL of deionized water to precipitate, and the pH was adjusted to 1 with hydrochloric acid; the precipitate was placed in 0.5 M sulfuric acid aqueous solution and heated under reflux for 12 h, washed with deionized water until neutral, and then redispersed in deionized water to obtain an aromatic carboxyl functionalized cellulose suspension; (4) After the aromatic carboxyl functionalized cellulose suspension obtained in step (3) is ultrasonically dispersed evenly, it is vacuum filtered and the cellulose is deposited on the surface of the filter paper to form a wet film. The wet film and the filter paper are dried at 60 °C for 8 min. After drying, the film is peeled off from the surface of the filter paper with tweezers to obtain a self-supporting membrane. The obtained membrane is then placed in 1 M potassium hydroxide solution and soaked at room temperature for 12 h for deprotonation and ion exchange treatment. Subsequently, the obtained membrane is washed with deionized water and soaked at least 3 times with deionized water, each soaking time not less than 6 h. After soaking, the obtained membrane is dried at 60 °C for 8 min to obtain an aromatic carboxyl functionalized cellulose membrane. Example 4
[0025] The preparation method of an aromatic carboxyl functionalized cellulose membrane according to this embodiment includes the following steps: (1) 1 g of cellulose was added to 36 mL of acrylonitrile, and 1 mL of 10% sodium hydroxide aqueous solution was added. The mixture was stirred magnetically at 30 °C for 12 h. After the reaction was completed, the mixture was neutralized with 10 mL of 1% acetic acid solution and washed with deionized water to obtain cyanoethylated cellulose. (2) The cyanoethylated cellulose obtained in step (1) was soaked in a mixed solution of 2 M hydroxylamine hydrochloride and 2 M sodium hydroxide for 2 h and stirred vigorously at 70 °C for 24 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water, and freeze-dried at -50 °C for 72 h to obtain aminooxime cellulose. (3) Disperse the aminooxime-modified cellulose obtained in step (2) in dimethyl sulfoxide to prepare a 2% dimethyl sulfoxide dispersion; add phthalic anhydride and react at 30 °C for 4 h, wherein the molar ratio of phthalic anhydride to aminooxime groups in aminooxime-modified cellulose is 5:1; then add potassium ethoxide and react at room temperature for 1 h, wherein the molar ratio of potassium ethoxide to aminooxime groups in aminooxime-modified cellulose is 13:1; after the reaction is completed, pour the reaction solution into 400 mL of deionized water to precipitate, and adjust the pH to 1 with hydrochloric acid; place the obtained precipitate in 1 M sulfuric acid aqueous solution and heat under reflux for 12 h, wash with deionized water until neutral, and then redisperse in deionized water to obtain an aromatic carboxyl functionalized cellulose suspension; (4) After the aromatic carboxyl functionalized cellulose suspension obtained in step (3) is ultrasonically dispersed evenly, it is vacuum filtered and the cellulose is deposited on the surface of the filter paper to form a wet film. The wet film and the filter paper are dried at 60 °C for 8 min. After drying, the film is peeled off from the surface of the filter paper with tweezers to obtain a self-supporting membrane. The obtained membrane is immersed in 2 M potassium hydroxide solution at room temperature for 12 h to carry out deprotonation and ion exchange. Then, the obtained membrane is washed with deionized water and soaked at least 3 times with deionized water, and the soaking time is not less than 6 h each time. After soaking, the obtained membrane is dried at 60 °C for 8 min to obtain an aromatic carboxyl functionalized cellulose membrane. Example 5
[0026] The preparation method of an aromatic carboxyl functionalized cellulose membrane according to this embodiment includes the following steps: (1) 1 g of cellulose was added to 36 mL of acrylonitrile, and 1 mL of 10% sodium hydroxide aqueous solution was added. The mixture was stirred magnetically at 25 °C for 12 h. After the reaction was completed, the mixture was neutralized with 10 mL of 1% acetic acid solution and washed with deionized water to obtain cyanoethylated cellulose. (2) The cyanoethylated cellulose obtained in step (1) was soaked in a mixed solution of 1.7 M hydroxylamine hydrochloride and 1.7 M sodium hydroxide for 2 h and stirred vigorously at 70 °C for 24 h. After the reaction was completed, the solid was collected by centrifugation, washed with deionized water, and freeze-dried at -50 °C for 72 h to obtain amine oxime cellulose. (3) Disperse the aminooxime-modified cellulose obtained in step (2) in dimethyl sulfoxide to prepare a 5% dimethyl sulfoxide dispersion; add phthalic anhydride and react at 30 °C for 4 h, wherein the molar ratio of phthalic anhydride to aminooxime groups in aminooxime-modified cellulose is 5:1; then add potassium ethoxide and react at room temperature for 1 h, wherein the molar ratio of potassium ethoxide to aminooxime groups in aminooxime-modified cellulose is 13:1; after the reaction is completed, pour the reaction solution into 400 mL of deionized water to precipitate, and adjust the pH to 1 with hydrochloric acid; place the obtained precipitate in 0.5 M sulfuric acid aqueous solution and heat under reflux for 12 h, wash with deionized water until neutral, and then redisperse in deionized water to obtain an aromatic carboxyl functionalized cellulose suspension; (4) After ultrasonically dispersing the aromatic carboxyl functionalized cellulose suspension obtained in step (3) evenly, vacuum filter it. The cellulose is deposited on the surface of the filter paper to form a wet film. Dry the wet film together with the filter paper at 60 °C for 8 min. After drying, peel the film off the surface of the filter paper with tweezers to obtain a self-supporting membrane. Soak the obtained membrane in 1 M potassium hydroxide solution at room temperature for 12 h to perform deprotonation and ion exchange. Then, wash the obtained membrane with deionized water and soak it at least 3 times with deionized water, each soaking time not less than 6 h. After soaking, dry the obtained membrane at 60 °C for 8 min to obtain an aromatic carboxyl functionalized cellulose membrane.
[0027] Comparative Example 1
[0028] Commercially available carboxycellulose nanofibers were added to deionized water and ultrasonically treated to disperse them evenly, resulting in a carboxycellulose nanofiber suspension. The suspension was then vacuum filtered to deposit the carboxycellulose nanofibers onto the filter paper surface to form a wet film. The wet film, along with the filter paper, was dried at 60 °C for 8 min. After drying, the film was peeled off from the filter paper surface to obtain an unmodified carboxycellulose nanofiber membrane, denoted as CNF-1.
[0029] The Fourier transform infrared spectra of CNF-1 prepared in Comparative Example 1 and CNF-Ph prepared in Example 1 are shown below. Figure 1 As shown. CNF-1 at 3000–3500 cm⁻¹ -1 A broad OH stretching vibration absorption peak appears at 1643, 1203, and 912 cm⁻¹, exhibiting characteristic absorption peaks of cellulose. Compared to CNF-1, CNF-Ph retains the aforementioned characteristic absorption peaks, indicating that the main chemical structure of the cellulose matrix is preserved after aromatic carboxyl functionalization and film-forming treatment; simultaneously, CNF-Ph shows absorption peaks at 1643, 1203, and 912 cm⁻¹. -1 The presence of new or enhanced characteristic absorption peaks related to the vibrations of groups such as C=O, CN, and NO within the range indicates that the oxadiazole-phenyl-carboxylic acid functional side chain has been introduced into cellulose.
[0030] The XRD pattern of the aromatic carboxyl functionalized membrane prepared in this embodiment is shown in the figure below. Figure 2 As shown. By Figure 2 It can be seen that CNF-1 prepared in Comparative Example 1 exhibits characteristic diffraction peaks of cellulose type I at 14.8°, 16.5°, and 22.6°, corresponding to (10), (110), and (200) crystal planes of cellulose type I, respectively. The aromatic carboxyl-functionalized cellulose membrane CNF-Ph still retains the characteristic diffraction peaks of cellulose type I (110) and (200) crystal planes at approximately 16.5° and 22.5° at 2θ, indicating that the aromatic carboxyl functionalization and film-forming treatment did not change the basic crystal form of cellulose, and the resulting membrane still has the cellulose type I crystal structure. The changes in the intensity and shape of the CNF-Ph diffraction peaks indicate that the introduction of aromatic carboxyl side chains has a certain influence on the ordered arrangement of cellulose molecular chains and the crystal structure.
[0031] SEM images and EDS elemental distribution maps of CNF-1 prepared in Comparative Example 1 and CNF-Ph prepared in Example 1 are shown below. Figure 3 As shown, the CNF-1 membrane has a relatively uniform surface structure, with interwoven fibers forming a continuous membrane structure. Compared to CNF-1, CNF-Ph also maintains a complete and continuous membrane structure with a relatively uniform surface morphology, and no obvious local aggregation was observed. EDS elemental distribution results show that the C and O elements on the CNF-1 membrane surface are relatively uniformly distributed, and the C, O, and N elements on the CNF-Ph membrane surface are also relatively uniformly distributed. The detection and uniform distribution of N element in CNF-Ph indicates that nitrogen-containing components have been introduced and uniformly distributed on the membrane surface. These results indicate that after aromatic carboxyl functionalization, the resulting membrane still has a uniform and continuous membrane structure, and no obvious local enrichment of nitrogen-containing components is observed, which can be Zn. 2+ This provides a structural basis for uniform transport and zinc anode interface regulation.
[0032] Application Example 1
[0033] The aromatic carboxyl functionalized cellulose membrane prepared in Example 1 was used as a test membrane for ionic conductivity, Tafel polarization, and Zn||Zn symmetric cell testing.
[0034] The membrane was thoroughly wetted with 2 M ZnSO4 electrolyte and then sandwiched between two stainless steel sheets to assemble a blocked electrode cell. The bulk resistance of the membrane was obtained by AC impedance spectroscopy, and its ionic conductivity was calculated. The test results are as follows: Figure 4 As shown, by Figure 4 It can be seen that the ionic conductivity of the CNF-Ph membrane is 4.33 mS / cm. -1 The value is higher than 2.62 mS cm⁻¹ of CNF-1 membrane. -1This indicates that the CNF-Ph membrane has superior ion transport capabilities.
[0035] A zinc sheet with a thickness of approximately 100 μm was cut into circular pieces with a diameter of 1 cm to serve as the zinc electrode. A separator, wetted with 2 M ZnSO4 electrolyte, was sandwiched between the two zinc sheets to assemble a Zn||Zn symmetric cell. Tafel polarization tests were performed, and the corrosion current density was obtained by Tafel extrapolation. The test results are as follows: Figure 5 As shown, by Figure 5 It can be seen that the corrosion current density corresponding to the CNF-Ph membrane is 1.5 mA cm⁻¹. -2 This is lower than the 5.7 mA cm⁻¹ of the CNF-1 membrane. -2 This indicates that the CNF-Ph separator can suppress the corrosion side reaction of the zinc anode and improve the stability of the zinc anode interface.
[0036] Further at 1 mA cm -2 Constant current deposition / stripping tests were performed on Zn||Zn symmetric cells at a current density, and the test results are as follows: Figure 6 As shown. By Figure 6 It can be seen that the symmetric cell using the CNF-Ph separator can cycle stably for 3500 h, while the symmetric cell using the CNF-1 separator shows significant voltage fluctuations or increased polarization in less than 200 h. These results indicate that the CNF-Ph separator can reduce ion migration resistance, suppress zinc dendrite growth and interfacial side reactions, thereby improving the deposition / stripping stability of the zinc anode.
[0037] Application Example 2
[0038] The aromatic carboxyl-functionalized separator prepared in Example 1 was assembled into a full cell as follows: MnO2 was used as the positive electrode active material in the battery, and the loading of the positive electrode sheet was 13.1~13.6 mg cm⁻¹. -2 After the positive electrode is prepared, a zinc sheet is cut to serve as the negative electrode. The zinc sheet used is 100 μm thick and cut into zinc discs with a diameter of 1 cm. A CR2032 button cell casing is used for full cell assembly. First, the zinc disc is placed inside the negative electrode casing; then, the aromatic carboxyl functionalized separator prepared in Example 1 is placed on the zinc disc. 150 μL of electrolyte is added to the separator using a pipette. The concentrations of ZnSO4, MnSO4, and Na2SO4 in the electrolyte are 2 mol·L⁻¹. -1 0.05 mol·L -1 and 0.1 mol·L -1After the separator is completely wetted by the electrolyte, the positive electrode is placed on top of the separator, and the positive electrode shell is closed. The battery is then pressed and packaged using a tablet press to obtain a CR2032 button cell. The assembled cell is allowed to stand at room temperature for 3 hours before electrochemical testing is performed under different rate conditions.
[0039] Test results are as follows Figure 7 As shown, when the current density increases from 1 A g -1 Gradually rising to 5 A g -1 At that time, the full cell assembled using CNF-Ph separators exhibited excellent rate performance at 1 A g. -1 2 A g -1 3 A g -1 4 A g -1 and 5 A g -1 At current densities of 262.4 mAh g, respectively, were observed. -1 204.8 mAh g -1 163.6 mAh g -1 131.3 mAh g -1 and 111.8 mAh g -1 The high reversible specific capacity indicates that the full cell assembled with CNF-Ph separator has a high reversible capacity, and CNF-Ph separator can improve the dynamic performance of the full cell.
[0040] The stability of the above-mentioned full cells was tested at 3 A g. -1 Cyclic experiments were conducted at current densities, and the results are as follows: Figure 8 As shown, by Figure 8 It can be seen that in 3 Ag -1 After cycling for 1000 cycles at a current density of 3A g, the capacity retention was 88.4%; -1 After cycling for 2000 cycles at a current density of 3 A g, the capacity retention was 82.3%; -1 After cycling for 3000 cycles at a current density, the capacity retention was 79.7%; 3 A g -1 After 4000 cycles at a current density, the capacity retention rate was 77.6%. The CNF-Ph membrane containing monobenzene ring side chains significantly suppressed zinc dendrite growth and interfacial side reactions by constructing a three-dimensional network structure with high ion transport capacity and interface regulation, reducing the generation of by-products, thereby improving the cycle stability and rate performance of aqueous zinc-ion batteries.
[0041] The above embodiments are used to further illustrate the technical solutions of the present invention and are not intended to limit the present invention. Equivalent substitutions, conventional modifications, or combinations of related technical features made by those skilled in the art based on the content disclosed in this specification, without departing from the technical concept of the present invention, should all fall within the protection scope of the present invention.
Claims
1. A method for preparing an aromatic carboxyl-functionalized cellulose membrane, characterized in that, Includes the following steps: (1) Cellulose was added to an aqueous solution of acrylonitrile and sodium hydroxide to carry out a cyanoethylation reaction. After neutralization and washing, cyanoethylated cellulose was obtained. (2) The cyanoethylated cellulose obtained in step (1) is reacted in a mixed solution of hydroxylamine hydrochloride and sodium hydroxide. After washing and freeze-drying, amine-oxime cellulose is obtained. (3) The aminooxime cellulose obtained in step (2) is dispersed in dimethyl sulfoxide, and phthalic anhydride and potassium ethoxide are added in sequence to react. After precipitation, acidification, reflux and washing in acidic aqueous solution, aromatic carboxyl functionalized cellulose product is obtained. (4) The aromatic carboxyl functionalized cellulose product obtained in step (3) is dispersed, filtered, dried to form a film and deprotonated in an alkaline solution, and finally washed and dried to obtain an aromatic carboxyl functionalized cellulose membrane.
2. The method for preparing the aromatic carboxyl functionalized fiber membrane according to claim 1, characterized in that, In step (1), the amount of cellulose used is 1~3 g, the amount of acrylonitrile used is 36~108 mL, the mass fraction of sodium hydroxide aqueous solution is 10%~15%, and the amount used is 1~3 mL; the temperature of the cyanoethylation reaction is 10~30 ℃, and the reaction time is 6~12 h; after the reaction is completed, acetic acid solution with a mass fraction of 1~3% is used for neutralization.
3. The method for preparing the aromatic carboxyl-functionalized cellulose membrane according to claim 1, characterized in that, In step (2), the concentration of hydroxylamine hydrochloride in the mixed solution is 1~2 M, and the concentration of sodium hydroxide is 1~2 M; after soaking the cyanoethylated cellulose in the mixed solution for 2~6 h, it is stirred and reacted at 70±10℃ for 24±12 h.
4. The method for preparing the aromatic carboxyl functionalized cellulose membrane according to claim 1, characterized in that, In step (3), the aminooxime cellulose is prepared into a dimethyl sulfoxide dispersion with a mass fraction of 2% to 5% aminooxime cellulose; the molar ratio of phthalic anhydride to the aminooxime group in the aminooxime cellulose is 1 to 10:1; the molar ratio of potassium ethoxide to the aminooxime group in the aminooxime cellulose is 1 to 20:
1.
5. The method for preparing the aromatic carboxyl-functionalized cellulose membrane according to claim 4, characterized in that, In step (3), after adding phthalic anhydride, the reaction is carried out at 10~30 ℃ for 2~6 h, and then potassium ethoxide is added and the reaction is carried out at room temperature for 0.5~3 h. After the reaction is completed, the mixture is precipitated with water, acidified with hydrochloric acid to pH 1~2, and then placed in a sulfuric acid aqueous solution with a concentration of 0.1~1.0 M and heated under reflux for 12±2 h.
6. The method for preparing the aromatic carboxyl-functionalized cellulose membrane according to claim 1, characterized in that, In step (4), the deprotonation treatment includes soaking in an alkaline solution, wherein the alkaline solution is at least one of sodium hydroxide solution and potassium hydroxide solution; the concentration of the alkaline solution is 0.1~2.0 M, and the soaking time is 0.5~12 h.
7. An aromatic carboxyl-functionalized cellulose membrane, characterized in that, The aromatic carboxyl functionalized cellulose membrane is prepared by the preparation method according to any one of claims 1 to 6.
8. The application of the aromatic carboxyl functionalized cellulose membrane according to claim 7 in the preparation of aqueous zinc batteries.
9. A battery, characterized in that, The battery includes the aromatic carboxyl functionalized cellulose membrane as described in claim 7.
10. The battery according to claim 9, characterized in that, The battery is a zinc symmetric battery or a zinc-ion full battery.